On developing a sustainable model of social work education in Ukraine - Hayduk, Nina; McKenzie, Brad (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. In the article, key stages of the Reforming Social Services: Canada-Ukraine Project (1999-2003) are described: as well, concepts are introduced and discussed as these relate to broad goals associated with social development. Purpose. The purpose of the article is to describe the development of the Social Work Program at Lviv Polytechnic National University and the unique nature of its partnership with community-based disability organizations. The quality and sustainability of the initiative following the end of CIDA funding are examined. Results. Social development was utilized as a framework for the design and implementation of the project. The project was conceptualized as a process that involved more extensive knowledge and human resource transfers to project activities in Ukraine in the early phase of implementation, a more collaborative form of partnership during the middle to late stages and the transfer of full power and control by the final stage. In the final stage and following the formal conclusion of the project it was recognized that Canadian partners would be acting more as consultants in response to requests from Ukrainian partners. The project impact was assessed in 2006 using a modified case study approach consisting of a review of social work literature in Ukraine, critical personal reflections on the effects of the program and focus group interviews and discussions with representatives from four primary stakeholders: agency-based field instructors, the Advisory Committee to the Social Work Program, social work instructors and social work students near the end of their program of studies. Evaluation feedback from the case study suggests that the goal of developing a sustainable social work education model has been achieved and that the development of supportive partnerships has been important to this outcome. Originality. Social development was used as a framework for the design and implementation of the Canada-Ukraine Project. Following the formal conclusion of the project its impact was evaluated using a modified case study approach. Conclusion. The social development framework with its emphasis on participatory approaches and partnerships is a useful guide in re-conceptualizing an approach to international social work education that includes a more critical approach to the adoption of western models of social work education. However, it is only through the application of principles emerging from this perspective that the framework moves beyond rhetoric and takes on real meaning.